PSIII-38 Effect of Deficiency or Surplus Dietary Energy Intake on the Onset of Puberty in Gilts Investigated by Liquid Chromatography-Mass Spectrometry Based Follicular Fluid Metabolomics Analysis. (7th December 2018) - Shi, M; Li, T; Wang, J
Abstract: The objective of this study was to investigate the effect of deficient or surplus dietary energy intake on the onset of puberty in gilts and the differential follicular fluid metabolites analyzed by liquid chromatography-mass spectrometry (LC-MS) metabolomics. A total of 72 Landrace x Large White crossbred gilts (Body weight, 84.0 ± 2.4 kg; Age, 150.4 ± 3.5 day) were used. Gilts were assigned to one of the three dietary treatments consisting of net energy values at 9.5, 10.4 and 11.2 MJ/kg, which represented deficient (DE), adequate (AE) and surplus (SE) dietary energy concentration, respectively. Estrus was checked using a back pressure test in the presence of a mature boar. Gilts with a standing response in front of the boar were identified as being in estrus. The estrus rate was recorded. At the day of first estrus, ovaries of gilts were collected. Metabolites in follicular fluid were identified by liquid chromatography-mass spectrometry. Our results indicated that the estrus rate was 54%, 91% and 58% for each treatment, respectively. Gilts fed diets with the AE diet had the greatest number of oocyte and highest oocyte quality (P < 0.01). Principal component analysis of the follicular fluid metabolites showed distinct separation among the three groups. Compared with the AE group, gilts fed the SE diet displayed a persistent decline in γ-aminobutyric acid (GABA), arachidonoyl-EA and estradiol. While the gilts fed the DE diet displayed a persistent decline included linolenic acid, oleamide and GABA. These changes in the follicular fluid are associated with disorders of energy metabolism as well as endocrine imbalances, which may contribute to the retardation of oocyte growth and development, and even lead to the delay of the onset of puberty.